2011
DOI: 10.1007/s11606-011-1689-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Problem-Solving-Based Diabetes Self-Management Training on Diabetes Control in a Low Income Patient Sample

Abstract: BACKGROUND: Lower socioeconomic status is associated with excess disease burden from diabetes. Diabetes self-management support interventions are needed that are effective in engaging lower income patients, addressing competing life priorities and barriers to selfcare, and facilitating behavior change. OBJECTIVE: To pilot test feasibility, acceptability, and effect on disease control of a problem-based diabetes self-management training adapted for low literacy and accessibility. DESIGN: Two-arm randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
145
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(148 citation statements)
references
References 25 publications
(32 reference statements)
1
145
0
2
Order By: Relevance
“…The majority of the interventions were educational programs on diabetes management delivered in-person, via telephone, or via computer multimedia. The remaining studies included medication management facilitation through contact with primary care providers (Crowley et al, 2013), and problem-solving training (Hill-Briggs et al, 2011). Regarding the study population, two studies recruited only participants with low health literacy (Moussa, Sherrod, & Original Article Choi, 2013;Negarandeh, Mahmoodi, Noktehdan, Heshmat, & Shakibazadeh, 2013).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the interventions were educational programs on diabetes management delivered in-person, via telephone, or via computer multimedia. The remaining studies included medication management facilitation through contact with primary care providers (Crowley et al, 2013), and problem-solving training (Hill-Briggs et al, 2011). Regarding the study population, two studies recruited only participants with low health literacy (Moussa, Sherrod, & Original Article Choi, 2013;Negarandeh, Mahmoodi, Noktehdan, Heshmat, & Shakibazadeh, 2013).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Health literacy was most commonly measured using the Short Test of Functional Health Literacy in Adults (STOFHLA) and the Rapid Estimate of Adult Literacy in Medicine (REALM). Only six studies selected patients according to a criterion of HbA1C level, which ranged from 6.5% to 8.0% (Cavanaugh et al, 2009;Hill-Briggs et al, 2011;Moussa et al, 2013;Schillinger, Handley, Wang, & Hammer, 2009). The outcomes measured in these studies were highly diverse.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in diabetes prevalence and treatment costs have led to a growing number of studies for controlling this disease. Many of these studies have suggested that diabetic patients care requires changes in their lifestyle and one of the most effective methods for the treatment and control of diabetes is an effective change in patient's condition and lifestyle (5)(6)(7)(8). Subsequently, self-care of diabetic patients and, also, changes in their life style require recognition and knowledge of patients about the principles of diabetic nutrition, monitoring of blood sugar levels and correct usage of insulin (9).…”
Section: Introductionmentioning
confidence: 99%
“…2 As such, great emphasis has been placed on implementing behavioral interventions targeting diabetes selfmanagement (DSM) education and skills, particularly among ethnic minority and low-income populations that bear a disproportionate burden of diabetes and have poorer glycemic control. 1 In this issue of the journal, Hill-Briggs et al 3 examined the feasibility, acceptability, and effectiveness of a problem-based, DSM training adapted for low literacy populations on glycemic control. They showed a significant change in hemoglobin A1c that was diminished by controlling for patient's problem-solving skills, suggesting that problem solving is a key component for glycemic control.…”
mentioning
confidence: 99%